Die funksies van die raad van beheer: Teorie en praktyk - Chris F. Van Veijeren (South African Journal of Business Management, 1983)
– The functions of the board of directors: Theory and practice A major difference seems to occur in practice between what the normally accepted functions of the board of directors are and what they actually do. As the ultimate body responsible for managing an organization, one would normatively expect them to set amongst other functions the strategy of the organization. Lack of detailed involvement, time and sometimes knowledge prevent them from actually doing so and it is argued that as far as strategy formulation is concerned, the board should perform an audit function to ensure that strategies are rationally set.
Keywords: 650